Research progress of hospice care in the Emergency Department (安宁疗护在急诊科应用的研究进展) - HOU Xiaowen (侯晓雯); YUE Yuzi (岳玉姿); HAN Jianping (韩建萍); YANG Yuwei (杨雨薇); SHI Ruyan (史茹嫣); DAI Wei (代巍) (中西医结合护理)
Hospice care provides all-round physical, psychological, social and spiritual care for terminally ill patients, with the ultimate goal of helping patients and their families get the best quality of life. It is a humanistic model of medical service. This paper summarizes the application status, influencing factors, application methods and specific methods of hospice care in the Emergency Department of hospitals at home and abroad, in order to promote the effective identification and management of hospice care patients, and provide reference for the development of hospice care in the Emergency Department. (安宁疗护基于全人照护理念, 为终末期患者提供涵盖身体、心理、社会和灵性4个维度的全方位照护。其核心目标是协助患者及其家属在生命的最后阶段获得最佳生活品质, 体现了一种人性化的医疗服务模式。本研究综合分析国内外急诊科安宁疗护的应用现状、影响因素, 并总结急诊科安宁疗护实践经验, 旨在促进对安宁疗护患者的精准识别与有效管理, 为我国急诊科安宁疗护服务的优化提供理论依据和实践参考。)